2021
DOI: 10.1108/jfm-03-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between political connections, auditor characteristics and auditor narcissism

Abstract: Purpose This study aims to assess the relationship between political connections, auditor characteristics (audit quality and industry specialization) and auditors’ intrinsic characteristics (narcissism) in listed firms on the Tehran Stock Exchange. In other words, this paper attempts to answer the question “whether political connections, audit quality and industry specialization contribute to the growth of narcissism and overconfidence of auditors of listed firms on the Tehran Stock Exchange or not.” Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There is a substantial empirical literature that examines the benefits and links between political connections and corporate financial outcomes. Several studies provide supporting viewpoints, and many empirical studies have revealed there are various benefits that help company performance as a result of government political connections (Bussolo et al, 2022; Khaksar et al, 2022a, 2022b; Salehi, 2020; Wu et al, 2018). One of them is easy access to financing.…”
Section: Institutional Background Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…There is a substantial empirical literature that examines the benefits and links between political connections and corporate financial outcomes. Several studies provide supporting viewpoints, and many empirical studies have revealed there are various benefits that help company performance as a result of government political connections (Bussolo et al, 2022; Khaksar et al, 2022a, 2022b; Salehi, 2020; Wu et al, 2018). One of them is easy access to financing.…”
Section: Institutional Background Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…People with high EI are able to make informed decisions, cope better with environmental demands and pressures, handle conflict effectively, communicate in an exciting and assertive manner, and make others feel better in their work environment (Love et al, 2011). Although the effects of team project leaders (Lennox et al, 2018), auditor overconfidence (auditor overconfidence), auditor narcissism (Khaksar et al, 2021), auditor resilience (Smith and Emerson, 2017), and auditors' psychological contract violation (Herrbach, 2001) on audit behavior have been explored in EI management research, the relationship between the audit steam's EI and reduced audit quality behavior has not been described. Therefore, the first key research question of this study is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…People with high EI are able to make informed decisions, cope better with environmental demands and pressures, handle conflict effectively, communicate in an exciting and assertive manner, and make others feel better in their work environment ( Love et al, 2011 ). Although the effects of team project leaders ( Lennox et al, 2018 ), auditor overconfidence (auditor overconfidence), auditor narcissism ( Khaksar et al, 2021 ), auditor resilience ( Smith and Emerson, 2017 ), and auditors’ psychological contract violation ( Herrbach, 2001 ) on audit behavior have been explored in EI management research, the relationship between the audit steam’s EI and reduced audit quality behavior has not been described. Therefore, the first key research question of this study is as follows.…”
Section: Introductionmentioning
confidence: 99%